(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The work defines the sigh as a type of breath expressing or communicating specific physical or mental internal states. To investigate the meanings of the sigh, the paper presents analyses of written and oral corpora, finding out that it may express different emotions like boredom or frustration, but also positive meanings like self-encouragement; then it focuses on the use of sighs in political debates. Finally a perception study shows participants’ agreement on the meanings of sighs in terms of valence and arousal. These results lay the bases for future studies to set a clearer distinction between sighs and other vocalisations as well as other effects on its meaning caused by the combination with other body signals like rolling eyes or shaking head.